2002
DOI: 10.1038/sj.eye.6700197
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and pathogenesis of retinal detachment

Abstract: Retinal detachment, separation of the neurosensory retina from the underlying retinal pigment epithelium, is a sight threatening condition that is considered one of the few ocular emergencies. The literature is enormously rich in studies that focused on different aspects of this disease process. Yet certain aspects remain largely unanswered. We briefly review major aspects of retinal detachment and discuss various important contributions in this field, focussing mainly on the pathogenesis of and predisposing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
160
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(179 citation statements)
references
References 93 publications
(93 reference statements)
2
160
1
2
Order By: Relevance
“…Cataract surgery is a major risk factor of RRD, due to the high rate of PVD after cataract extraction and a lower hyaluronic acid concentration causing vitreous collapse [21,22]. A previous study found that although only 2.4% of the population underwent cataract surgery, 43% of patients with RRD had a history of cataract extraction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Cataract surgery is a major risk factor of RRD, due to the high rate of PVD after cataract extraction and a lower hyaluronic acid concentration causing vitreous collapse [21,22]. A previous study found that although only 2.4% of the population underwent cataract surgery, 43% of patients with RRD had a history of cataract extraction [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is referred to separation of the neurosensory retina form the underlying retinal pigment epithelium [6]. Clinically, it presents with variable visual loss [7].…”
Section: Discussionmentioning
confidence: 99%
“…Silicone oil plays an outstanding role in the management of complex vitreoretinal surgical procedures (12). During silicone oil tamponade, the concentration and release of injected drugs into the posterior segment is unpredictable, however, Bevacizumab injection was found effective for the management of iris neovascularization associated with TRD by several authors (13). Additionally, to the best of our knowledge, the effect of concomitant treatment of silicone oil and bevacizumab after vitrectomy rarely was reported in the literature (14).…”
Section: Introductionmentioning
confidence: 99%